Government Budget Absorption: A Study on The Reallocation and Refocus of the COVID-19 Budget - Yesi Mutia Basri; Gusnardi Gusnardi; Hariadi Yasni (Universitas Pendidikan Ganesha, 2021)
Low absorption of Covid 19 budget causes problems for the government. This study examines the influence of regulation, budget execution, utilization of information technology, and leadership commitment to the absorption of the Covid 19 budget in the Provincial Government of Riau. The population in this study were all Regional Apparatus Organization (OPD) in the Riau Provincial Government. The sampling technique used is purposive sampling with OPD criteria using the Covid 19 budget. Respondents in this study are budget managers. A total of 68 people participated in this study. Data analysis with PLS shows that regulation, budget implementation, and the use of information technology affect the absorption of the Covid 19 budget. Meanwhile, the leadership's commitment does not affect the absorption of the Covid 19 budget. This research has contributed to the Riau Provincial government in formulating budget use policies.